2018
DOI: 10.1590/1678-5150-pvb-4389
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização epidemiológica da leptospirose suína em criações não tecnificadas do semiárido brasileiro

Abstract: RESUMO: Este estudo foi realizado em suínos do município de Mossoró, Rio Grande do Norte, com o objetivo de caracterizar epidemiologicamente a leptospirose suína em criações não tecnificadas do semiárido brasileiro. Para isso, foi realizado diagnóstico sorológico da infecção pela técnica de soroaglutinação microscópica (SAM), sendo as amostras submetidas a uma coleção de 24 variantes de leptospira, e foram obtidas informações, por meio de visitas às criações e entrevistas com os proprietários, abordando variáv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The difference between the seropositivity values can be explained by the location of the studies and the type of breeding adopted by the producers. Valença et al [ 47 ], who established 16.1% seropositivity, carried out their survey on technically swine farms in the state of Alagoas, Brazil, while Leite et al [ 41 ], who reported 78.6% seropositivity, developed the study in non-technified farms in Mossoró, in the state of Rio Grande do Norte, Brazil. These results demonstrate that technical care applied correctly is effective in reducing the infectious agent in swine production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between the seropositivity values can be explained by the location of the studies and the type of breeding adopted by the producers. Valença et al [ 47 ], who established 16.1% seropositivity, carried out their survey on technically swine farms in the state of Alagoas, Brazil, while Leite et al [ 41 ], who reported 78.6% seropositivity, developed the study in non-technified farms in Mossoró, in the state of Rio Grande do Norte, Brazil. These results demonstrate that technical care applied correctly is effective in reducing the infectious agent in swine production.…”
Section: Discussionmentioning
confidence: 99%
“… Combined evaluation of twenty studies on the seropositivity of leptospirosis in pigs [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. …”
Section: Figurementioning
confidence: 99%
“…However, a serum positive for a single pathogenic serovar and Patoc cannot be considered as such. Furthermore, it is important to note that carriers, even in low numbers, can rapidly disseminate the pathogen throughout the herd, especially in a suitable (humid) environment for pathogen development [13,30,38]. The severity of Leptospira spp.…”
Section: Discussionmentioning
confidence: 99%
“…The total number of samples was determined using the EpiInfo software, considering a total population size of 4917 animals. The estimated expected frequency was 78.6%, based on the findings from the research of Leite (2018) [30]. To achieve a 95% level of reliability within a margin of expected error of 5%, with a design effect of 1 and considering clusters of 188, it was necessary to collect a minimum of two samples per property, totaling 376 serum samples.…”
Section: Sample Design and Study Areamentioning
confidence: 99%
See 1 more Smart Citation